PENGARUH COVID-19 TERHADAP PEKERJAAN PERIAS PENGANTIN DI YOGYAKARTA - Herina Yuwati; Triwarsi Hapsari (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2020)
ABSTRACT This study aims to find out how far the impact of the Covid-19 pandemic has on the work of brides and grooms in Yogyakarta. This research includes descriptive research types and tends to use descriptive analysis. In this study, the determination of research subjects was determined by sampling techniques, while the object studied was the work of brides during the Covid-19 Pandemic. Data collection techniques are carried out with interviews, observations, and documentation. Interviews and observations are used to obtain detailed data about the influence of bridal work due to the Covid-19 Pandemic. While the documentation is used to describe the real form of the work of the bride and groom at this time. The data is analyzed with descriptive analysis techniques. The results of the analysis showed that the Covid-19 Pandemic is so influential on the work of brides and grooms that they temporarily switch professions